Ontogenic changes in the feeding habits of the fishes Agonostomus monticola (Mugilidae) and Brycon behreae (Characidae), Térraba River, Costa Rica - Thiago Cotta-Ribeiro; Helena Molina-Ureña (Revista de Biología Tropical, 2009)
Las dietas de los peces varían con respecto a la calidad, la cantidad y el tamaño del alimento. Esta variación puede deberse a factores como la estacionalidad y la fase del desarrollo del individuo. Estudiamos los cambios ontogénicos en los hábitos alimentarios de dos peces dulceacuícolas, Agonostomus monticola y Brycon behreae, de la Cuenca del Río Térraba, Pacífico sur de Costa Rica. Ambas poblaciones son omnívoras, pero con cambios ontogénicos en la cantidad y calidad de los ítemes consumidos. Conforme crecía, A. monticola modificó su dieta de insectívora hacia un mayor consumo de materia vegetal, asociado con un aumento en la longitud relativa del intestino. Aunque mantuvo su dependencia de alimentos vegetales, B. behreae diversificó su dieta de dos formas. Primero, pasó de partes suaves de plantas a semillas, hojas y frutos. Luego, los ítemes cambiaron de insectos hacia una dieta más carnívora (peces y camarones). Estos hallazgos para ambas especies enfatizan la importancia de proteger la vegetación riparia de estos ecosistemas tropicales. Fish diets can vary in food quality, quantity and size. The variation can be caused by several factors, including season and the ontogenic phase of the individual (McCormick 1998). We studied the ontogenic changes in feeding habits of two freshwater fishes, Agonostomus monticola and Brycon behreae, from the Térraba River basin, South Pacific of Costa Rica. Both populations were omnivorous, but displayed ontogenic shifts in terms of quantity and quality of the food items consumed. As it grew, A. monticola modified its diet from insectivorous towards a higher consumption of vegetables, which was accompanied by an increase in relative length of the intestine. While remaining dependent on vegetation as staple food, B. behreae diversified its diet in two ways. Initially, from soft plant parts to seeds, leaves, and fruits. Secondly, prey items changed from insects into a more carnivore diet (fish and shrimp). These findings for both species stress the importance of protecting riparian vegetation in these tropical ecosystems. Rev. Biol. Trop. 57 (Suppl. 1): 285-290. Epub 2009 November 30.